Streptococcal Throat Carriage among Primary School Children Living in Uyo, Southern Nigeria - Edem, Kevin B.; Ikpeme, Enobong E.; Akpan, Mkpouto U. (Journal of Child Science, 2021)
Surveillance of the carrier state for β-hemolytic streptococcal (BHS) throat infections remains essential for disease control. Recent published works from Sub-Saharan Africa have suggested a changing epidemiology in the burden of BHS throat infections. The objective of the present study was therefore to determine the prevalence and pattern of BHS throat carriage in school-aged children in Uyo, Akwa Ibom State. This was a prospective cross-sectional study of 276 primary school children in Uyo. Subjects were recruited by multistage random sampling. Obtained throat swabs were cultured on 5% sheep blood agar. Lancefield grouping on positive cultures was done by using the Oxoid Streptococcal Grouping Latex Agglutination Kit, United Kingdom. Antimicrobial susceptibility testing was done with the disk diffusion method. Associations were tested with Fischer's exact test. The prevalence of BHS carriage was 3.3%. Group C Streptococcus was identified in 89% of isolates and Group G Streptococcus in 11%. Younger age and larger household size were associated with asymptomatic streptococcal throat infections. Antimicrobial susceptibility was highest with cefuroxime and clindamycin (89% of isolates each), while 78% of isolates were susceptible to penicillin. None of the tested isolates was susceptible to co-trimoxazole. The prevalence of streptococcal throat carriage in the study area was low. There were no Group A Streptococcus isolates suggesting an evolving epidemiology of BHS disease in the study area.
Keywords: β-hemolytic streptococci; group A streptococci; throat carriage; surveillance